2014
DOI: 10.1016/j.drugalcdep.2013.10.025
|View full text |Cite
|
Sign up to set email alerts
|

First-year college students’ interest in trying dissolvable tobacco products

Abstract: Background Dissolvable tobacco products (DTPs) have been introduced into test markets in the U.S. We sought to gauge level of interest in trying these products and correlates of interest among potential consumers. Methods A web-based survey of freshman at 11 universities in North Carolina (NC) and Virginia (VA) was conducted in fall 2010. Multivariable logistic regression analyses were used to identify correlates of students’ likelihood to try DTPs. Results Weighted prevalence of likelihood to try DTPs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Since the aim of the overall study was to assess trajectories and correlates of smokeless tobacco use among college students, those who were at higher risk for using smokeless tobacco were oversampled, including lifetime smokeless tobacco users, current cigarette smokers, and males. A total of 3146 students participated in The Smokeless Tobacco Use in College Students Cohort Fall 2010 Survey and were recruited into the cohort (36,37). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the aim of the overall study was to assess trajectories and correlates of smokeless tobacco use among college students, those who were at higher risk for using smokeless tobacco were oversampled, including lifetime smokeless tobacco users, current cigarette smokers, and males. A total of 3146 students participated in The Smokeless Tobacco Use in College Students Cohort Fall 2010 Survey and were recruited into the cohort (36,37). …”
Section: Methodsmentioning
confidence: 99%
“…The sixth survey was fielded in Fall 2013. The protocol was approved by the Wake Forest School of Medicine Institutional Review Board and the Institutional Review Boards of participating institutions where requested (36,37). …”
Section: Methodsmentioning
confidence: 99%
“…Point-of-purchase assessments were conducted during the study, Smokeless Tobacco Use among College Students Wolfson et al, 2014). We assessed the environmental landscape of tobacco promotion around college campuses by completing assessments at 15 tobacco retailers in each community.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, 4,902 freshmen were invited to participate from the screener survey with 3,146 completing the survey for a response rate of 64.2%. 29 Cohort participants completed surveys in the fall and spring of their first 2 years of college and then annually (in the fall) during the third and fourth years. Reasons for not completing a survey were not assessed.…”
Section: Samplementioning
confidence: 99%
“…Additional details about the parent study can be found elsewhere. 28,29 To identify potential members of the cohort, a screener survey of all freshmen was conducted at the 11 colleges in the fall of 2010. 28 Overall 10,528 freshmen completed the screener (response rate of 35.6%).…”
Section: Samplementioning
confidence: 99%